Service Quality influence on Customer Satisfaction and Brand Loyalty: An Empirical Study on Pakistan Airline Industry (KASBIT Business Journal, 2023)
The airline industry’s intensifying competition has encouraged companies to pursue a shared objective to attain customer satisfaction and establish brand loyalty. Companies recognize the crucial role that service quality and customer satisfaction play in retaining customers and gaining an edge over rivals in the market. As such, the significance of prioritizing service quality has amplified in this increasingly competitive environment. This paper aims to find out whether service quality (ServQual) results in customer satisfaction and does it mediate service quality towards brand loyalty through mediation in Pakistan’s airline industry. Additionally, the objective is to identify the service quality dimensions that exerts the most significant influence on customer satisfaction. The research was carried out using a quantitative approach by administering survey from recent travelers of local air carriers. The study demonstrates that in Pakistan’s airline industry, all dimensions of service quality, except for empathy, has a significant effect on customer satisfaction. The assurance being the most significant dimension contributing to the variation in customer satisfaction levels. Furthermore, the research reveals that customer satisfaction has a partial mediating role between ServQual and its impact on brand loyalty. This paper illustrates that service quality should be given more importance to increase repeat purchase intention of the customers.
Keywords: Airline Industry; SERVQUAL; Brand Loyalty